Digitally Dismantling Asian Authoritarianism: Activist Reflections from the #MilkTeaAlliance. Issue 1 (1st June 2021) - Dedman, Adam K.; Lai, Autumn
Abstract: In April 2020, a Twitter war erupted under the hashtag #MilkTeaAlliance. It united users from Thailand, Taiwan, and Hong Kong in a fight against Chinese techno-nationalists' attempts to shame public figures into supporting the Chinese Communist Party (CCP)'s framing of geopolitics. In the months that followed, Thai, Taiwanese, and Hong Kong activists continued to lend support to each other through their use of this and other hashtags. Why does the #MilkTeaAlliance hashtag resonate with so many? What political contexts preceded the consolidation of the #MilkTeaAlliance, and how may this alliance reshape geopolitical landscapes offline? We approach these questions from our perspective as activists embedded in these movements. We argue that the formation of the #MilkTeaAlliance unites voices that are marginalized diplomatically, discursively, and affectively by the CCP, and—more crucially—generates valuable affective and physical forms of intra-Asian solidarity against authoritarianism in the region.